(untitled) (Pakistan Journal of Science, 2022)
This study was made to determine the effects of herd, year, season, lactation number and sex on calf’s birth weight in Nili Ravi Buffalo. The data from 1975-2017 was taken in 15525 edited observations of 6932 buffaloes from six institutional herds. The year was divided into four seasons viz (December to February, March to May, June to August and September to November) to evaluate the real effects of herd x year and season. To analyze the data SPSS version 19, statistical package was used. The mean ± S.E of birth weight was calculated as 35.18±.018Kg. The mean of birth weight of male and female calf were as 35.82 ± 0.19Kg and 34.53 ± 0.18Kg, affected by herd-yearseason, sex and lactation number (P<0.01) while the effect of gestation period and age of dam was non-significant. The sex ratio between male and female was 51.25 and 48.74 respectively. It was observed that calf’s birth weight had significant effect on milk production.